Peran BPOM Kota Pekanbaru Dalam Mengawasi Perdagangan Kosmetik Illegal: Universitas Islam Riau - Ramailis, Neri Widya; Wandi, Deki Putra (Sisi Lain Realita, 2018)
This Research study about Observation Of Bpom Town of Pekanbaru To supervison Cosmetic of Illegal in Town of Pekanbaru. Aim research is to know how observation done/conducted by BPOM to commerce of cosmetic of illegal in Town of Pekanbaru. research this of method use of qualitative Descriptive. Data technique collecting by doing/conducting direct observation, interview with precise documentation of time,Objective and totally , centrally at dots observation of strategic, Realistic economically, Realistic organizationally. Result of research of showing observation of BPOM to Commerce of Cosmetic of illegal in Town of Pekanbaru do not walk optimal caused by the lack of human resource to do/conduct observation , Schedule implementation of observation disagree with inexistence and rule of sansi coherent to owner of distribution medium which is order breaking. Its of him that is renewing data sum up and existence of cosmetic distribution medium, giving socialization, coaching, examination more public often, publish of cosmetic warning in printing / book , doing/conducting progam by exploiting media of internet like instrgram, facebook, as well as recruitment yahoo, do to then observation.